La performance des images - Dierkens, Alain; Bartholeyns, Gil; Golsenne, Thomas (Problèmes d'histoire des religions, 2010)
The image, before representing, to signify, acts and makes act. The performance of images, which this book undertakes exploration, is to be understood first of all as the evaluation of their effectiveness: what are the effects of images? It is then their agency: in what way are images living beings? It is also their performativity: as there are acts of speech, there are acts of image whose modalities can be detailed. Finally, it is their power: what can an image, including a text, for example, be incapable? Christian image holds a special place here because, far from being a simple "Bible of illiterate "subject to the reign of the text, it permeates all aspects of the life and thought of Christian societies, from their theological and anthropological foundations - God created man in his image; the Son is the image of the Father - up to the most diverse uses of visual objects. But in the West it is not only in the Middle Ages that the images are active: this book is also devoted to the new forms of visual performances that appeared with the Renaissance or the mass-media society.